Mengedukasi Pernikahan di Bawah Umur Menurut Undang-Undang Perkawinan No. 1 Tahun 1974” - Minan Minan; Teguh Endi Widodo; Tutik Asmorowati; Ruminingsih Ruminingsih; M. Fikri Jauhari; Daryuti Daryuti (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Child marriage remains a serious problem in Indonesia despite the revision of the Marriage Law, which raised the minimum age for marriage to 19 for both men and women through Law No. 16 of 2019. This practice remains widespread, especially in rural areas with a high prevalence due to economic and cultural factors, the existence of marriage dispensation mechanisms, and low legal literacy. The phenomenon of child marriage has multidimensional impacts, including reproductive health risks, high school dropout rates, low quality human resources, economic vulnerability, and psychological problems that can ultimately lead to high divorce rates and intergenerational structural poverty. Through Community Service Activities (PKM), prevention efforts are carried out by providing legal education and outreach regarding the risks of early marriage. Methods used include lectures, presentations, modeling, role plays, and small group discussions involving teenagers, parents, traditional leaders, and religious leaders. The results of the activities showed a significant increase in legal understanding, where 85% of participants were aware of the minimum age for marriage according to the latest regulations. Furthermore, there was increased awareness of the negative impacts of child marriage and a growing commitment from community leaders to continue ongoing outreach. The conclusion of this activity confirmed that marriage law education is an effective strategy in raising public awareness. However, preventing child marriage cannot rely solely on legal outreach; it needs to be strengthened through cross-sector collaboration, integration of materials into the school curriculum, family economic empowerment, and strengthening the role of religious and traditional leaders in shaping social opinion. Therefore, efforts to prevent early marriage require a more holistic, participatory, and sustainable strategy to protect children's rights and realize the development of a quality future generation.